Peningkatan Partisipasi Politik Pemilih Pemula melalui Preferensi Politik Media Sosial pada Pemilu 2024: Incerasing the Political Participation of Beginning Voters through Social Media Political Preferences in the 2024 Election - Ummah, Siti Muslikhatul; Munandar, Moh. Aris; Arumsari, Nugraheni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This article focuses on social media activities by beginning voters at SMAN 12 Semarang City for forming their political preferences of the 2024 election. Social media activities are one way to fulfill information needs, including political information, especially ahead of the 2024 election. The purpose of the article is to report the benefits of social media in providing political preferences to beginning voters to determine their choice in the 2024 election. The method of implementing this activity is carried out socialization to class XII students. The output of this activity is in increasing beginning voters' knowledge of political actors participating in the election through the use of social media.